Lean Transformation Integrated with Industry 4.0 Implementation Methodology - Satoglu, Sule; Ustundag, Alp; Cevikcan, Emre; Durmusoglu, Mehmet Bulent (Springer International Publishing, 2017)
Succeeding a cultural and people-oriented transformation, lean producers adopt the philosophy of doing more with less by eliminating non-value-added activities from production processes to maintain effectiveness, flexibility, and profitability. In the context of Industry 4.0, new solutions are available for combining automation technology with lean production. Moreover, when effective usage of resources (finance, labor, material, machine/equipment) is concerned, it is obvious that Industry 4.0 should be applied to lean processes. In this context, this paper attempts to emphasize the interaction between lean production and Industry 4.0 and proposes a methodology that provides guidance for Industry 4.0 in a lean production environment. Moreover, Industry 4.0 technologies and automation-oriented lean production applications are also included.